Tata Kelola Pariwisata Berkelanjutan dengan Konsep Ekowisata Berbasis Kearifan Lokal - Widyaningtyas, Widyaningtyas (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
Ecotourism, an alternative kind of travel that places a higher priority on protecting the environment and the natural world by enhancing the ecology of a tourist destination, is promoted since improper management of tourism development can have unfavorable effects. The goal of this project is to leverage local knowledge to establish development plans for Ponggok Village as a freshwater tourist destination. The quantitative method was the research strategy employed in this investigation. The quantitative approach determines the best course of development given the features of Ponggok Village, Klaten, by utilizing the Importance Performance study (IPA) study to explain the relationship between performance levels and importance levels. The study's development path enhances performance on the most crucial elements and refers to the area's strength factor as a feature of the tourist attraction. In order to transform Ponggok Village into a freshwater ecotourism area based on local wisdom, three development directions have been formulated: (1) preserving and enhancing the ecosystem of the tourist attraction area in accordance with Ponggok Village's unique characteristics; (2) expanding the scope of tourism object management services by applying social norms and values; and (3) optimizing spatial and land planning at tourist attractions, which results in the formation of ecotourism area functions based on local wisdom.